2018
DOI: 10.17116/jnevro20181183132-38
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory hypercapnic-hypoxic training is an effective component of complex therapy of polyneuropathy in children with diabetes type 1

Abstract: Hypercapnic exercises significantly contribute to the pathogenetic therapy of diabetes mellitus and polyneuropathy in this disease, have a significant clinical effects reducing serum concentrations of fasting glucose and severity of neurological deficit scores on the NIS-LL, increasing the speed of conduction of excitation through the nerves, reducing the residual latency of EMG activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For example, in a randomized triple-blind placebo-controlled study, respiratory training with hypercapnic hypoxia was shown to have a positive effect on the functional state of the nervous system in children with cerebral palsy and can be used as a means to increase the effectiveness of standard therapy for these patients [187]. Additionally, the effectiveness of hypercapnic hypoxia has been demonstrated in the treatment of diabetic polyneuropathy in pediatric patients [188]. Such efficacy is likely associated with the high neuroplasticity and adaptogenic potential in childhood [189].…”
Section: Future Directions and Potential For Clinical Applicationmentioning
confidence: 99%
“…For example, in a randomized triple-blind placebo-controlled study, respiratory training with hypercapnic hypoxia was shown to have a positive effect on the functional state of the nervous system in children with cerebral palsy and can be used as a means to increase the effectiveness of standard therapy for these patients [187]. Additionally, the effectiveness of hypercapnic hypoxia has been demonstrated in the treatment of diabetic polyneuropathy in pediatric patients [188]. Such efficacy is likely associated with the high neuroplasticity and adaptogenic potential in childhood [189].…”
Section: Future Directions and Potential For Clinical Applicationmentioning
confidence: 99%
“…The available literature lacks information on the effect of hypoxia and especially hypercapnia on diabetes mellitus and carbohydrate metabolism. Smirnov et al showed that hypercapnic-hypoxic training (2 hours a day) reduces blood glucose levels and promotes the treatment of type 1 diabetes mellitus and concomitant polyneuropathy in children [67].…”
Section: Life Extensionmentioning
confidence: 99%